Cyclic carbonates in the synthesis of biodegradable polymers - Plichta, A.; Florjańczyk, Z.; Rokicki, G. (Polimery, 2022)
In the literature review most important results of studies on biodegradability of aliphatic polycarbonates and copolymers of cyclic carbonates (ethylene carbonate or trimethylene carbonate) with heterocyclic monomers have been presented. A new idea about mechanism of poly(ethylene carbonate) degradation in vivo in the presence of peroxide anion-radical initiating the chain depolymerization leading to ethylene carbonate and further to CO2 and ethylene glycol [equation (4)] has been discussed. In the part concerning authors’ research the results of homopolymerization of various heterocyclic monomers [among others propylene oxide (POX), ethylene carbonate (EC), trimethylene carbonate (TMC), L-lactide (L-LA)] catalyzed with methylaluminoxane (MAO) (Table 1) were presented. The polymers were investigated using 1H NMR (Fig. 1), 13C NMR (Fig. 2) and MALDI TOF (Figs. 3, 4) methods. It was demonstrated that in the presence of MAO the products showing the linear as well as cyclic structures were formed. Formation of macrocyclic oligomers shows the presence of some electrophilic centers in MAO structure, which lead to the reaction of back-bitting type. L-lactide and racemic lactide were copolymerized with EC or terpolymerized with EC and POX in the presence of various catalysts (MAO, MAO modified with ZnEt2, Et2AlOEt - Table 2). The products obtained contained up to 6.5 % of carbonate units maximally. L-LA/EC copolymer with the highest content (6.5 wt. %) of carbonate mers was obtained in the presence of MAO modified with ZnEt2.